Optimizing SCoT-PCR Parameters for Reproducible Genetic Diversity Analysis in Cassava, Rice, Maize, and Foxtail Millet - Yudiansyah Yudiansyah; Ismiyanti Ismiyanti; Susilawati Susilawati; M Reza Pahlevi; Sintho Wahyuning Ardie (Department of Agronomy and Horticulture, IPB University, 2026)
Technical optimization of PCR parameters is essential to ensure efficiency and accuracy in genetic analyses. The performance and reproducibility of Start Codon Targeted (SCoT) markers are strongly influenced by annealing temperature (Ta) and primer concentration. Raising Ta from 50 °C to 55 °C reduced both amplicon yield and reproducibility, whereas higher primer concentrations increased amplicon counts without substantially affecting reproducibility. Optimal amplification was achieved at Ta 50 °C with a primer concentration of 2.5 μM, where most primers produced high amplicon numbers with 100% reproducibility. Evaluation of 36 SCoT primers in foxtail millet identified 20 primers with full reproducibility, of which 10 were further tested across cassava, rice, and maize. Primer reproducibility varied among species, and only SCoT‑35 and SCoT-36 consistently achieved 100% reproducibility across all three crops. These results highlight that primer suitability is species‑dependent and emphasize the need for extensive primer screening in each plant species. Overall, optimizing Ta and primer concentrations, combined with careful primer selection, is essential for the reliable, efficient, and cost-effective application of SCoT markers in plant genetic diversity analysis.